Activation of trace amine-associated receptor 1 attenuates schedule-induced polydipsia in rats. (January 2019) - Sukhanov, Ilya; Dorotenko, Artem; Dolgorukova, Antonina; Hoener, Marius C.; Gainetdinov, Raul R.; Bespalov, Anton Yu.
Abstract: Trace Amine Associated Receptor 1 (TAAR1) is a novel pharmacological target. TAAR1 are well-documented to play a modulatory role in the dopaminergic system. In spite of a growing number of studies of TAAR1 effects, little is still known about the behavioral pharmacology of TAAR1 ligands, including effects of repeated TAAR1 agonist administration. The present study appears to be the first that estimated the action of TAAR1 agonists on schedule-induced polydipsia, a type of adjunctive behavior, which is considered to be useful for evaluating certain aspects of obsessive-compulsive and related disorders (OCD) and schizophrenia. Our results have demonstrated that the wide range of RO5263397, the highly selective partial TAAR1 agonist, doses (1–10 mg/kg) attenuated the polydipsia induced by two different schedules of food delivery in rats. The effect remained unchanged for the 7 days of repeated treatment. However, the highest tested doses of RO5263397 (6 and 10 mg/kg) decreased the vertical locomotor activity of the animals and the volume of water intake of thirsty rats following the acute treatment. Also, though, the repeated RO5263397 administration is exhibited to diminish the volume of consumed water and weight of rats without SIP, on the other hand, the tolerance was observed to these drug effects. In general, the RO5263397 decreases specifically the adjunctive drinking and this effect is maintained with repeated drug administration without the development of tolerance. The interpretation of these results as an evidence for the RO5263397 anticompulsive-like action, however, should be taken with caution because the drug also influenced the drinking behavior and only weakly affected the other parameters of SIP used to reveal the potential anticompulsive-like effects of drugs. Highlights: RO5263397, the highly selective partial TAAR1 agonist, attenuated SIP in rats. This effect of the highest tested doses can be affected by non-specific drug effects. The RO5263397 repeated administration did not influence the SIP-attenuating effect.